Customer service, service, product and price as determining variables of customer satisfaction in a service SME. (GEON Journal (Management, Organizations and Business), 2019)
Service quality has become very important in recent years in all businesses, because customers currently have very high expectations and skills are higher, as each company tries to match or exceed these expectations. Good quality services must be offered and anticipated to respond to a broad range of customer needs. Service quality is not only about how to manage a product, but how to serve customers before and after handling. That is why quality in the service is used in organizations as a tool for differentiation.
Keywords: Quality; Satisfaction; Customer; Client; Business